Physical Properties of (Basalt-Ni) System by Thermal Spray Flame Technique (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Many surfaces suffer cracks and external corrosion such as turbo blades and oil pipes. In order to solve these problems are used coatings of high durability and low cost. In the current research, the power of the basalt with multiple oxides supported by metal (Ni) 50% was sprayed models with thermal spraying by flame and at multiple spraying distances of (10,12,14,16,18,20) cm after the preparation of the models coated on a base of alloy steel, the process of sintering of the samples at (700, 900, 1100) ℃ and within two hours have been done. The mechanical tests were (strength adhesion, porosity, hardness, wear, and tear) (SEM) for prepared samples before and after sintering. The results showed that the best spraying distance was 16 cm and the best heat treatment is ( (1100 ℃), depending on the results of the adhesion strength tests at (24.43 MPa) and (8.653%) porosity, (1140 Hv) and the hardness of the Vickers and at a constant sliding speed (12000 cm/min). The results of the scanning electron microscopy showed clear surface consistency after thermal conductivity with a few pores and treatments the best (1100.).